Investigation of Genetic Variations using Microsatellite Markers in Colored Horses in Turkey - Koseman, A.; Ozsensoy, Y.; Erdogan, M.; Yarali, C.; Toprak, B.; Zengin, K.; Seker, I (Maik Nauka/Interperiodica/Springer, 2020)
The aim of this study was to determine the genetic variation of Colored horses by using microsatellite markers. In the study, samples from a total of 28 Colored horse were genotyped using 17 microsatellite markers, 12 of them are recommended by the International Society for Animal Genetics (ISAG) and the other 5 loci included by the StockMarks Genotyping Kit. A total of 129 different alleles were identified and the average number of alleles was 7.588.The heterozygosity value (H-o) was 0.286 as the lowest (LEX3) and 0.929 (HTG10) as the highest among the markers; the expected lowest heterozygosity value (H-e) was determined as 0.607 (HTG4) and the highest one was 0.876 (VHL20). The mean H-o and H-e values were calculated as 0.729 and 0.771, respectively. On a population basis, the mean F-IS and F-IT values were 0.047. The mean PIC value was 0.741. In the phylogenetic tree formed by the neighbour joining tree (NJT), it was determined that the horses were generally categorized into 3 groups. Although statistically significant results (P = 0.01008) were found in the studies investigating whether the population of Colored horses had the risk of extinction or not, it was determined that the data showed normal L distribution indicating no risk of recent extinction. It was determined that the Colored horses had a genetically important potential.
Keywords: bottleneck; colored horse; genetic variation; microsatellite; phylogenetic tree